Self-reported chronic conditions in student population in Slovenia - Klemenc-Ketiš, Zalika (Zdravniški vestnik, 2010)
Purpose/Objective: The aims of this study were (1) to determine the prevalenceof chronic diseases in a student population in Slovenia, (2) to determine the eff ects of chronic diseases on the use of health services. Methods: A cross-sectional web-survey among university students in Ljubljana and Maribor, Slovenia took place in March and April 2008. Data were analyzed using SPSS version 13.0 (SPSS Inc, Chicago, IL, USA),and chi-square test, t-test and binary logistic regression analysis were performed. Results: Th e prevalence of chronic diseases in the student population was 40.3 %. Th e mostcommon chronic diseases were allergies (excluding hay fever) (14.9 %), hayfever (11.4 %), followed by skin diseases (9.2 %) and anxiety (5.3 %). Bothhigh blood pressure and asthma had a higher prevalence in men than in women (p < 0.001 and p = 0.023, respectively). Students with chronic conditions less oft en thought that they can infl uence their own health by self-treatment, experienced stress in the previous week, more likely visited or contacted his/her personal doctor in the past year, more likely purchased medications for self-treatment from a pharmacist in the past year, were more aware of the facts that self-treatment may hide the symptoms and signs of illness to such extent that the doctor may not be able to recognize it or overlook it completely. Conclusion: A greater awareness of the prevalence and impact of chronic diseases in students is warranted and the existing interventions should be changed in order to achieve a better life quality of university students.
Keywords: ankete; chronic condition; Chronic Disease; Cross-Sectional Studies; Epidemiology; Kronična bolezen; kronične bolezni; Kvaliteta življenja; Presečne študije; Prevalenca; Prevalence; Quality Of Life; Questionnaires; Samooskrba; Self Care; student; Students; Študenti